Ex-users: přínosy a rizika jejich práce s drogově závislými klienty - Schulzová, Daniela (Univerzita Karlova, Filozofická fakulta, 2014)
This bachelor thesis is devoted to ex-users, who after a successful recovery from drug addiction started to devote their time working in organizations that help drug addicts. In the theoretical part, I start to explain the basic overview of the addiction. This includes the type of drugs used, how they are administered and the effects they have on individuals. I also chart the different options available in the treatment of drug addiction. The larger part of the thesis delves into the therapeutic treatments available and places particular emphasis on treatment in therapeutic community as well as what are the expected qualities of the therapist. I have collated a lot of informations from different experts in their field on the effects of the addition on drug addicts. The research part of the thesis is based on interviews with ex-users who work with drug addicts. It looks to ascertain what the benefits are and the risks involved in working with drug addicted clients. The research also looks to find what motivates an ex-users to work with addicted clients, how they view their own addiction and if any lessons are being learned from their encounters. Also, how they now view their own profession after successfully recovering from drug addiction. In conclusion, this thesis evaluates how successful the research into. Tato bakalářská práce se věnuje ex-userům, kteří po úspěšném vyléčení ze závislosti začali pracovat v některém ze zařízení pro drogově závislé klienty. V teoretické části uvádím základní pojmy z drogové sféry, popisuji rozdělení drog a jejich účinků a také možnosti a druhy léčby, přičemž větší prostor věnuji léčbě v terapeutické komunitě a požadovaným vlastnostem terapeuta. Rovněž přináším názory na ex- usery z pohledu odborné literatury. Ve výzkumné části se snažím prostřednictvím rozhovorů s ex-usery a jejich následné analýzy zjistit, jaké jsou přínosy a rizika jejich práce s drogově závislými klienty, jaká byla jejich motivace pro práci v této oblasti a jak vnímají sami sebe a svoji zkušenost se závislostí ve vztahu ke své současné profesi. V závěru práce pak zhodnocuji, jak dalece byly naplněny cíle výzkumu a zodpovězeny výzkumné otázky. Powered by TCPDF (www.tcpdf.org) Katedra sociální práce Department of Social Work Faculty of Arts Filozofická fakulta